Nitrogen mineralization in soils cultivated with plantain (Musa AAB Subgroup plátano cv. Hartón), Zulia state, Venezuela - González-Pedraza, Ana Francisca; Carlos Escalante, Juan (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The main source of N in the soil is organic matter; therefore, its availability depends on its quantity and quality, microbial activity, soil characteristics and management. An efficient way to quantify available N is by mineralizing it as ammonium (N-NH) and nitrate (N-NO). Therefore, in this study, the total and available N was determined in soil samples 0-20 cm deep from two plots with plantain plants (Musa AAB plantain subgroup cv. Hartón) with high and low vigor (AV and BV, respectively), in the South of Lake Maracaibo. Total N was determined by the Kjeldalh method and the mineralization of available N by incubation under laboratory conditions for 10 weeks. The accumulated mineralized N (Nm), the constant mineralization rate of (k) and the potentially mineralizable N (N0) were calculated. A one-way analysis of variance was applied, when it was significant (p<0.05), a Tukey test was applied for multiple comparisons of means. Total N was low (<0.025 %) and did not present statistical differences (p<0.05) between AV and BV. The accumulated mineralized N-NO was statistically (p<0.05) higher (524.47 mg.kg-1) in BV, while the N-NH did not present differences between AV and BV. Only k was statistically higher (0.07 ± 0.03; p<0.05) in BV. Nitrification was the process that prevailed especially in BV where organic carbon was higher and presented a higher percentage of sand.